Antisocial Behavior at Age 37: Developmental Trajectories of Marijuana Use Extending from Adolescence to Adulthood - Brook, Judith S. (2011)
This investigation studied the association between developmental trajectories of marijuana use extending from adolescence to age 32 and later antisocial behavior at age 37. Semi-parametric group-based modeling and logistic regression analyses were used to analyze the data. Five distinct trajectories of marijuana use were identified: never-users, quitters/decreasers, occasional users, chronic users, and increasing users. Being either a chronic user or an increasing marijuana user was associated with an increase in the risk of exhibiting antisocial behavior in adulthood. Both chronic and increasing use of marijuana may serve as predictors of adult antisocial behavior. Treatment programs to prevent antisocial behavior across the life course should include a component to address earlier and concurrent marijuana use.